Development of impedimetric DNA sensor for diagnosis of Human Papillomavirus type 18 infection - Correr, Wagner Rafael (2014)
Currently, the most common strategy employed to detect DNA sequences is PCR (Polymerase Chain Reaction). Nevertheless, in the last few years research on DNA biosensors has increased significantly. Such sensors represent an alternative to PCR in the detection of specific DNA sequences, once they exhibit fast response, low limits of detection, and require simpler sample preparation. The development of a biosensor for detection of DNA from Human Papillomavirus type 18 is reported. To immobilise DNA probe onto indium-tin oxide (ITO) electrodes, a silanisation was carried out using 3-Aminopropyltryethoxysilane (APTES). Silanisation was studied and optimised using ultra-violet absorption spectroscopy, atomic force microscopy, fluorescence microscopy, and cyclic voltammetry. After immobilisation, the hybridisation with target sequence is detected by changes in surface properties of ITO electrode by Cyclic Voltammetry and Electrochemical Impedance Spectroscopy, using the Ferri-Ferrocyante redox couple. The detection of synthetic target sequence was performed in the range of 12.5 to 100 nM, and 300nM for PCR products. The sensor did not show significative response for non-complementary sequence at 50 nM. This sensor can be applied for fast and low cost detection of HPV genetic material at nanomolar levels.